Pengembangan Kualitas Generasi Ideal Perspektif Al-Quran dan Sosiologi - Fajar, Muhammad (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
The rapid advancement of technology often has a negative impact on civilisation. The younger generation, who are predicted to be the successors, are now suffering from various challenges and various social deviations. The progress of civilisation, which is often only oriented towards the sophistication of innovation and industry, often leads to moral aridity and loss of norms. On the other hand, the Quran holds all the social dimensions related to the ideal generation that can advance civilisation. This research uses the content analysis method with a focus on examining the indications or substantial messages in the verse and linking them to the social context. The results found are, 1) important elements of the ideal generation in the Quran include; physical, intellectual, mental-spiritual, and emotional aspects. 2) solutions that can be extracted are the importance of the role of family parenting, community participation and government policy. Abstrak Melesatnya kemajuan teknologi sering kali turut membawa dampak buruk bagi peradaban. Generasi Muda yang digadang-gadang menjadi penerus, kini didera berbagai tantangan dan pelbagai penyimpangan sosial. Kemajuan peradaban yang kerap hanya berorientasi pada kecanggihan inovasi dan industri sering kali justru menyebabkan gersangnya moral dan hilangnya norma. Di sisi lain, Alquran menyimpan segenap dimensi sosial terkait generasi ideal yang dapat memajukan peradaban. Penelitian ini menggunakan metode analisis konten dengan fokus mencermati indikasi atau pesan substansial dalam ayat dan mengaitkannya dengan konteks sosial kemasyarakatan. Hasil yang ditemukan adalah, 1) elemen penting generasi ideal dalam Alquran di antaranya; aspek fisik, intelektual, mental-spiritual, dan emosional. 2) solusi yang dapat diekstrak adalah pentingnya peran pola asuh keluarga, peran serta masyarakat dan kebijakan pemerintah.